Edukasi Pengenalan Instrumen Investasi Keuangan Bagi Warga Desa Di Desa Air Joman Kecamatan Air Joman Kabupaten Asahan - Suriana; Andri Ekawati, Yuni; Subaktiar; Irawan, Deni; Rivani, Tia; Azizah (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
This community service activity takes the form of education on the introduction of financial investment instruments aimed at providing knowledge and insight to the residents of Air Joman village regarding various financial investment instruments. Research results show that on average Indonesian people carry out savings and investment activities using only 13% of their income. This can be concluded that Indonesian people still have low awareness regarding the importance of investing. The target audience for this community service activity was the villagers in Air Joman village, with approximately 14 people attending. Education regarding the introduction of financial investment instruments is carried out using lecture and question and answer methods. The lecture method is used to explain introductory concepts of financial investment. Meanwhile, the question and answer method provides participants with the opportunity to discuss further the material that has been presented.